Problemas aritméticos de enunciados verbales para desarrollar la resolución de problemas de cantidad en estudiantes de segundo grado de primaria - Vásquez Salinas, María Del Rosario (2023)
The purpose of this sufficiency work is to develop the competence Solve quantity problems through the application of the strategy Arithmetic problems of verbal statements in students of the second grade of primary school. As a methodology, a set of learning sessions that will allow the improvement of student learning to be recognized and validated through the application of learning activities were planned, executed and evaluated. The PAEV strategy is based on the constructivist theory, the problem-solving approach and is currently attached to the competency-based approach. It was concluded that this strategy developed the resolution of quantity problems, showing better performance in the second grade students in the area, finding the result of problems more efficiently, proposing better strategies in solving their problems and representing the data and your operation.